The Old Testament Dietary Laws Was Abolished According To Mark 7:19b? - Harman Ziduhu Laia; Jimmy Sutrisno; Daniel Ari Wibowo (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2022)
Various essential discussions have been raised against Mark's parenthetical commentary in 7:19b, one of which is the discussion of eating from that statement. On the one hand, some take the text as a clear teaching of the Bible about the abolition of the food law in the Torah, as a result of which the law no longer binds both Jewish believers and Gentile believers. On the other hand, some consider it meaningless as the abolition of the food law in the Torah. Within this group, various meanings have been proposed. Historically, lexically, grammatically, and contextually it shows that Mark 7:19b is not a teaching of the abolition of the food law in the Torah, but a